On Multiperiod Stochastic Dominance - Huang, C. C.; Vertinsky, I.; Ziemba, W. T. (Journal of Financial and Quantitative Analysis, 1978)
Following Markowitz's [11] pioneering work on portfolio selection, it is customary to consider an individual's choice among several risky assets as a two-step procedure. First, given some general characteristics concerning his preferences, the decision maker chooses an efficient set of portfolios independent of his specific preference assessment. Secondly, an optimal portfolio is chosen from the efficient set given the individual's specific preferences.